Inclusive and Sustainable Management of Suboptimal Lands for Productive Agriculture in Indonesia - Benyamin Lakitan (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2014)
There are uncountable research activities and technology development efforts have been carried out in Indonesia; however, very limited economically and/or socially beneficial technologies have been created. Very few indigenous technologies have been used in producing goods and providing services, including in agricultural sector. This problem is rooted on facts that most of the technologies developed are not relevant to real needs and/or problems of domestic farmers. Even if the technologies are substantially relevant; in many cases, they are not finacially affordable by domestic farmers, do not significantly increase profit if used, and/or less competitive compared to similar available technologies in the market. Limited availability of resources, at present and even more scarse in the future, elevates expectation on technology to contribute in establishing inclusive, productive, and sustainable agricultural development. To assure that developed technology will be relevant to the needs and contribute to agricultural development, farmers ought to be play significant active roles during priority setting, planning, and developing the technology. The real issues at present are increase in food demand as consequence of population growth and conversion of arable lands for uses in other sectors. These trends have led to intensifying agricultural activities on suboptimal lands. Efforts to increase agricultural productivity in suboptimal lands should not jeopardize sustainable function of the ecosystem and participation of local farmers. Sustainability and inclusivity should be maintained while increasing productivity. Traditional knowledge and local wisdom have to be treated as reference for developing technology for establishing productive agriculture on suboptimal lands.